Experience of the treatment of combat injuries of the maxillofacial area with titanium implants in the conditions of modern war - D. V. Ivchenko; S. D. Varzhapetian; O. M. Mishchenko; O. V. Sydor; Yu. M. Petrenko; Ye. V. Yatsun; T. V. Strohanova (Patologìâ)
The aim. To research some features of a combat injury of the jaw-facial region and possible options of surgical treatment using titanium implants.